The mediation and facilitation of a ‘living' landscape through the musical arts within the Clanwilliam Arts Project - Andrews, Brandon Hilton (College of Music, 2023)
The Clanwilliam Arts Project, situated in Clanwilliam, Western Cape, South Africa, is a community arts initiative that has become a platform for many artists, scholars, and students. Gaining access to the town creates an opportunity to engage with the town's culturally rich history, knowing that the Clanwilliam region is often referred to as an archaeological gem with its archaeological field station housed at the Living Landscape, Park Street. The community arts project has also been known as a training centre for students and artists in community-based arts learning, exposing them to the practice of informing and enriching a community about its heritage. The objective of the study was to investigate the ways in which the mediation and facilitation of a ‘living' landscape took place through the arts with specific emphasis on the musical arts. The rich ancestral history of Clanwilliam, along with its own practices of community-making through the arts, were engaged with the lenses of tradition, culture, and heritage. To accommodate this culturally rich context provided by the Clanwilliam Arts Project, a multidimensional theoretical framework was implemented. The overall theoretical framework consisted of an amalgamation of three ‘theories' by three different authors: • Huib Schippers's Twelve Continuum Transmissions Framework (2010) • Meki Nzewi's principle of space within an African ensemble context (2005) • Sylvia Bruinders's perspective on ‘hidden subjectivities' (2017). For these three theories to form a conceptual whole, an additional theory was introduced to integrated them, namely Harry Garuba's Roots and routes: Tracking form and history in African diasporic narrative and performance (2010). Following a constructivist paradigm, this qualitative study made use of interviews, observations, and biographical questionnaires. The analysis of the qualitative data employed a grounded theory approach that enabled patterns and themes to emerge accordingly. Following the theoretical framework, findings from the review of literature and fieldwork data were used in collaborative form to assist the study's key findings. Analysing the processes involved in facilitating and mediating the ‘living' landscape in community-based learning through the musical arts context has revealed that the Clanwilliam community is to be considered as a peripheral field of learning. Key findings indicated that, with the mediation and facilitation of a ‘living' landscape, communities coexist and cohabituate in this peripheral field of learning when the past is reconnected and/or reimagined with the present.